Pemekaran Nagari: Transformasi Desa Adat di Kabupaten Pesisir Selatan - Kei Nishikawa (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2023)
This article discusses the changes and continuities in the structure and function of nagari, Minangkabau â€œtraditionalâ€ village. Many scholars consider nagari as an autonomic â€œvillage republicâ€ which was ruled by local leaders based on customary law. Even though nagari has been incorporated into the national administrative structure during colonial and post-independence of Indonesia, nagari is still regarded as the source of legitimacy on customary law. Especially in the 2000s, nagari has given more authority in the national legal system in Indonesia. In this article, I describe how nagari in Pesisir Selatan, West Sumatra is divided into smaller units. In order to get more budgets for village management from central government, local leaders and village heads chose to divide the nagari into smaller villages administratively but maintained large nagari informally as a single community bound by customary law. Interestingly, the new administrative villages are also called â€œnagariâ€ and are given authority on customary law. This created a situation in which formal smaller but administrative nagari co-exists with larger yet informal nagari. What are the consequences of this dualism? By analyzing the process of nagari division, I describe how several different notions of â€œnagariâ€ have developed in one village.